Promoting International Competitiveness for Small and Medium-Sized Enterprises (SMEs): A Case Study of Chinese SMEs in Thailand - Weihao Wu; Narissara Parkvithee (International Review of Management and Marketing, 2017)
The purpose of this study is to explore the problems faced by Small and Medium Enterprises (SMEs) in Thailand, particularly among Chinese SMEs. The study also seeks to identify how these difficulties impact on factors, both external and internal, which influence the business competitiveness of these SMEs. This paper further suggests guidelines for promoting international competitiveness of Chinese SMEs and other ethnic subsidiaries in Thailand. Qualitative analysis using semi-structured interviews was conducted. Content analysis was employed to analyze the data and describe the contingency phenomenons that occur in business environments associated with SMEs in Thailand. The findings suggest that some of the key macro environment factors that have a bearing on Chinese SME firms' competitiveness include market competition, the legal and political environment, and the social and cultural environment including language used to communicate with consumers. The study also indicates that internal factors like the SME firms' capabilities of enterprise management, brand management, marketing, their effective deployment of human resources, and innovation are likely aspects that can contribute to the firms' successful performance rather than financial performance in the global marketplace.